PREPARATION OF CONDUCTIVE MEMBRANES BY CHEMICAL IN SITU POLYMERIZATION OF POLYPYRROLE ON CELLULOSE FIBERS - Duc Dong, Tran; Duc Tung, Dao; Hoang Van, Bui; Dinh Quang, Nguyen; Dinh Tu, Bui; Thi Thao, Vu; Duc Cuong, Nguyen (HNUE Journal of Science: Journal of Natural Sciences, 2024)
The development of flexible electronic devices, particularly flexible and bendable energy storage devices, has catalyzed significant interest in the research of flexible composite materials. In this study, conductive paper membranes were synthesized by polymerizing polypyrrole (PPy) on the surface of cellulose fibers. The cellulose material, derived from cardboard, underscores an eco-friendly approach to waste reduction and environmental protection. Characterization of the cellulose/PPy conductive membranes using Fourier-transform infrared spectroscopy (FT-IR), field-emission scanning electron microscopy (FE-SEM), and differential scanning calorimetry (DSC) confirmed the formation and uniform coverage of PPy on the cellulose surface. To enhance the uniformity of PPy polymerization on cellulose relative to previous studies, this work focuses on elucidating the formation and deposition of PPy particles on cellulose fibers, leading to the development of a homogeneous membrane. The membrane exhibited a peak electrical conductivity of 18.04 mS/cm at 0.1 mA, with conductivity increasing alongside PPy concentration, albeit at the expense of mechanical properties. Additionally, the membrane demonstrated charge storage capability, with specific capacitance values ranging from 22.5 to 50 pF/cm2 at a frequency of 1 kHz. The uniformity of PPy coverage on the cellulose surface was a crucial factor influencing the electrical properties of the composite membrane. This research highlights the significant potential of conductive membranes for application in flexible and bendable energy storage devices.